THE LATEST TRENDS IN ARCHITECTURE IMPORTANT FOR SUSTAINABLE DEVELOPMENT AND ENVIRONMENTAL PROTECTION - Mihajlovic, Predrag; Mihajlović, Marija (Journal of process management and new technologies, 2018)
In this paper, the emphasis will be on presenting the trends that are dominant in the field of construction in 2017. Includes projections built around the world, from fantastic transport containers that have been adapted and converted into a residential proctor to the skyscraper in the true sense of the word. In addition, the emphasis is on those construction projects that were built with the intention of protecting the environment as well as according to the principles of sustainable development.